O-12 The influence of patient covariates on insulin dose-requirements in children newly diagnosed with type 1 diabetes mellitus. Issue 10 (20th September 2017) - Müller,; Al-Sallami,; Wheeler,; Blackwell,
Abstract : Background: Type 1 diabetes mellitus (T1DM) is a com-mon chronic illness of childhood. Insulin is the mainstay of therapy and in order to maintain glycaemic control, the dose is adjusted frequently based on the patient's blood glucose until a stable dose is achieved. Guideline recommendations in regard to the initial total daily dose of insulin (TDD) at new onset of disease vary two-fold (0.5 to 1.0 IU/kg/day). The aim of the study was to identify the influence of patient covariates on the dose-requirement of insulin in newly diagnosed children and adolescents with T1DM. Methods: A retrospective chart review of children admit-ted to hospital over a five-year period due to new onset T1DM was undertaken. Demographic, clinical, insulin dosing, and laboratory data were recorded. The influence of patient characteristics on insulin TDD was analysed sta-tistically by performing univariate and multivariate linear regression analyses. Results: Clinical and insulin administration records for 70 patients were available for analysis. The median age of subjects was 9 years and median duration of admis-sion was 6 days. The median insulin TDD on first day of admission was 21 units (0.7 U/kg) and that of the day be-fore discharge was 27 units (1 U/kg). In the multivariate regression analysis, body size (total body weight and fat-free mass), HbA1C, and blood ketone concentration were found to be significant predictors for the target TDD (p<0.05). Conclusion: In addition to body weight, HbA1c and ke-tone concentrations may be helpful in calculating initial TDD in newly diagnosed children with T1DM. This will potentially decrease the number of days needed to reach a stable dose and result in improved early glycaemic control. These findings may be used to study a larger cohort of patients in order to quantify the influence of these co-variates on dose-requirements.